Toxoplasmosis-related knowledge among pregnant and postpartum women attended in public health units in Niterói, Rio de Janeiro, Brazil - Millar, Patricia Riddell (2014)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Toxoplasmose. Rio de Janeiro, RJ. Brasil / Universidade Federal Fluminense. Departamento de Microbiologia e Parasitologia. Niterói, RJ, Brasil.